Youth Crime in Karachi and London: A Comparative Analysis (Since 1990-2000) - Muhammad Ahmed Qadri; Muhammad Arshad (European Scientific Journal, ESJ, 2020)
This paper focuses on performing a comparative analysis of youth crime in London (UK) and Karachi (Pakistan). The methodology adopted to carry out this research was of a descriptive study. The researcher on the basis of qualitative and quantitative findings has found the prevalence of juvenile delinquency in the different societies. It was found that even though the society of the UK possesses better mechanism and structure in the form of education, social lifestyle, police and law enforcing agencies, Britain is still faced with considerable challenges in minimizing juvenile delinquency within the Kingdom, specifically in London. The same has also been identified in the case of Pakistan where the situation and rate of juvenile delinquency are constantly increasing. This is due to various factors such as its economic condition, education standard, standard of living and others. It is, however, recommended that societies should make significant reforms in education, social, and other sectors in order to deal with the issue more effectively.